2012
DOI: 10.1021/cm203194v
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Pathway of Crystallization of Zeolite ZSM-5 in a Heterogeneous System: Phenomenology and Starting Considerations

Abstract: Crystallization of zeolite ZSM-5 from a diluted heterogeneous system (12.5Na 2 O−Al 2 O 3 −8TPABr−60SiO 2 − 4000H 2 O) was investigated by various experimental methods such as X-ray diffraction (XRD), electron diffraction (ED), infrared spectroscopy (FTIR), X-ray fluorescence (XRF), scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), thermo-gravimetric analysis (TGA), particle size analysis (PSA), pH measurement, inductive coupling plasma (ICP) emission sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
127
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(139 citation statements)
references
References 74 publications
11
127
1
Order By: Relevance
“…This is consistent with the finding that the amorphous phases obtained by ball-milling of zeolites A and X contain residual nano-sized quasicrystalline particles that cannot be detected by XRD, but can be identified by IR [21]. The nanoparts then act as nuclei for crystallization of LTLtype SAPO which can grow either in the amorphous matrix [22][23][24] or in the liquid phase after their releasing from the dissolved parts of the amorphous phase [25][26][27]. However, since the product (LTL-type SAPO) appear as discrete particles (crystals; Fig.…”
Section: Hydrothermal Conversion Of Sapo-37 Into Ltl-type Saposupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with the finding that the amorphous phases obtained by ball-milling of zeolites A and X contain residual nano-sized quasicrystalline particles that cannot be detected by XRD, but can be identified by IR [21]. The nanoparts then act as nuclei for crystallization of LTLtype SAPO which can grow either in the amorphous matrix [22][23][24] or in the liquid phase after their releasing from the dissolved parts of the amorphous phase [25][26][27]. However, since the product (LTL-type SAPO) appear as discrete particles (crystals; Fig.…”
Section: Hydrothermal Conversion Of Sapo-37 Into Ltl-type Saposupporting
confidence: 89%
“…However, since the product (LTL-type SAPO) appear as discrete particles (crystals; Fig. 6) rather than polycrystalline aggregates [22][23][24], it is reasonable to assume that the nanoparts grow into LTL-type SAPO in the liquid phase, i.e., after their release from the amorphous matrix [25][26][27]. Fig.…”
Section: Hydrothermal Conversion Of Sapo-37 Into Ltl-type Sapomentioning
confidence: 99%
“…3g. This confirms that the gel mass reached equilibrium at 2 h. The morphology of the gel walls resembled the open dendritic gel structure and the worm-like particles (WLP) reported by Valtchev [16] and Subotić [17], respectively.…”
Section: Gel Structure At Equilibriumsupporting
confidence: 84%
“…In particular, two similar porous morphologies have been reported recently for the gel aggregates in systems with moderate concentration leading to ZSM-5. An open dendritic gel structure was first reported by Valtchev and colleagues [16] and a closely related structure depicted as consisting of worm-like particles (WLP) was later reported by Subotić and colleagues [17]. Both groups have clearly evidenced that lower silica/alumina ratios favor thicker structures with larger particles [16,17].…”
Section: Introductionmentioning
confidence: 93%
“…These processes are hypothesized to involve the breakage and formation of Si-O-Si and Si-O-Al bonds. 31 The concept of "gel transformation" has been proposed for zeolites such as ZSM-5 (MFI), [32][33][34] zeolite A (LTA), 35 and zeolite X/Y (FAU). 36,37 For LTA, it was suggested that nucleation occurs within the interior of the gel, followed by crystal growth (from the gel interior to its exterior) by consuming nutrient within the gel particle.…”
Section: Introductionmentioning
confidence: 99%